2011
DOI: 10.7589/0090-3558-47.4.945
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in the Arctic Fox Population, Svalbard, Norway

Abstract: ABSTRACT:Arctic foxes, 620 that were trapped and 22 found dead on Svalbard, Norway (1996Norway ( -2004, as well as 10 foxes trapped in Nenets, North-West Russia (1999), were tested for rabies virus antigen in brain tissue by standard direct fluorescent antibody test. Rabies antigen was found in two foxes from Svalbard and in three from Russia. Blood samples from 515 of the fox carcasses were screened for rabies antibodies with negative result. Our results, together with a previous screening (1980-1989, n5817) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In these low-density Arctic fox populations, immigration caused sporadic outbreaks of rabies, which is reflected by a strong correlation between the immigration rate of infectious Arctic foxes and cumulative density of rabies cases in sensitivity analysis. This result is consistent with empirical data from Svalbard, Norway, where episodic rabies cases in a relatively low-density Arctic fox population appear to be caused by the infrequent introduction of the virus by a small number of long-distant migrants coming from Russia (Mørk et al 2011). This important potential role of immigration and long-distance movement in rabies dynamics and persistence in the Arctic suggests that metapopulation modelling or spatially explicit simulation approaches may be key avenues for future research.…”
Section: Immigration Of Infectious Arctic Foxes and Interaction With supporting
confidence: 90%
See 1 more Smart Citation
“…In these low-density Arctic fox populations, immigration caused sporadic outbreaks of rabies, which is reflected by a strong correlation between the immigration rate of infectious Arctic foxes and cumulative density of rabies cases in sensitivity analysis. This result is consistent with empirical data from Svalbard, Norway, where episodic rabies cases in a relatively low-density Arctic fox population appear to be caused by the infrequent introduction of the virus by a small number of long-distant migrants coming from Russia (Mørk et al 2011). This important potential role of immigration and long-distance movement in rabies dynamics and persistence in the Arctic suggests that metapopulation modelling or spatially explicit simulation approaches may be key avenues for future research.…”
Section: Immigration Of Infectious Arctic Foxes and Interaction With supporting
confidence: 90%
“…When rabies virus is no longer circulating locally in the Arctic fox population, new rabies outbreaks could be triggered by the reintroduction of the virus following immigration of infected Arctic foxes from other areas (Mørk & Prestrud 2004). The role of migrants in reintroducing rabies to regions where it has died out is also supported by genetic studies of the Arctic rabies virus variant that suggest disease spread by Arctic foxes travelling across the sea ice from Russia to Svalbard (Mørk et al 2011) and from North America to Greenland (Mansfield et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The link between the cyclic occurrence of rabies outbreaks in Arctic fox populations reported here and in related studies is often reported as being correlated to fox population density, relying in part on cyclic variations in prey abundance, e.g., rodents (Ballard et al 2001;Dalén et al 2005;Norén et al 2011b). When Arctic fox populations peak in numbers, the likelihood of encounters between individuals increases once the foxes disperse (Tabel et al 1974;Mørk and Prestrud 2004;Mørk et al 2011). Studies on dispersal distances in Canada (Tarroux et al 2010) and Russia (Goltsman et al 2005) indicate that movement distances of more than a thousand kilometers are not uncommon in Arctic foxes.…”
Section: Discussionmentioning
confidence: 96%
“…Red foxes from the Norwegian mainland do not get in direct contact with arctic foxes in Svalbard, but the red fox population may have contact with other European wildlife populations (Norén et al, 2015). One explanation for the arrival of the virus to Svalbard can be through migration of arctic foxes from other Arctic regions, as suggested for other pathogens arrived in Svalbard from Russia (Henttonen et al, 2001, Mørk et al, 2011. It is known that arctic foxes in Svalbard get in contact with other high-Arctic wildlife populations by using the sea ice as platform for migration (Geffen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%